2018
DOI: 10.1002/mnfr.201800160
|View full text |Cite
|
Sign up to set email alerts
|

The Endotoxemia Marker Lipopolysaccharide‐Binding Protein is Reduced in Overweight‐Obese Subjects Consuming Pomegranate Extract by Modulating the Gut Microbiota: A Randomized Clinical Trial

Abstract: Consumption of PE decreased endotoxemia in overweight-obese individuals by reshaping the gut microbiota, mainly through the modulation of Faecalibacterium, Odoribacter, and Parvimonas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 62 publications
2
75
1
Order By: Relevance
“…In a recently published study with these 49 overweight–obese individuals (trial 2) whose endotoxemia marker lipopolysaccharide‐binding protein (LBP) and blood cholesterol were reduced by pomegranate extract consumption, Parvimonas and Methanobrevibacter were also reduced. Furthermore, plasma LBP reduction was associated with Parvimonas decrease . However, associations between the decrease of LBP values and individuals’ UMs was not found while cholesterol reduction was higher in UM‐B volunteers .…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In a recently published study with these 49 overweight–obese individuals (trial 2) whose endotoxemia marker lipopolysaccharide‐binding protein (LBP) and blood cholesterol were reduced by pomegranate extract consumption, Parvimonas and Methanobrevibacter were also reduced. Furthermore, plasma LBP reduction was associated with Parvimonas decrease . However, associations between the decrease of LBP values and individuals’ UMs was not found while cholesterol reduction was higher in UM‐B volunteers .…”
Section: Discussionmentioning
confidence: 75%
“…Gut microbiota analysis was carried out in the fecal samples at baseline. Protocols for bacterial DNA isolation, 16S rDNA gene amplification, metagenomic sequencing library preparation Illumina (Illumina Inc., San Diego, CA, USA) as well as sequence processing and taxonomic classification of gut microbiota were carried out in the same lab (in a centralized manner) as described previously . Paired‐end sequencing with a read length of 2 × 300 bp was carried out using a MiSeq Reagent kit v3 (MS‐102‐3001) on a MiSeq‐Illumina platform (FISABIO sequencing service, Valencia, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, transplantation of bacteria isolated from a pair of twins, one obese and the other thin, to germ‐free mice resulted in mirrored response to the donors . Although limited, emerging evidence indicates that the anti‐obesity efficacy of many pharmaceutical agents and dietary supplements, including single agents such as melatonin, and mixtures/extracts or whole plants such as Ganoderma lucidum and Gegen Qinlian Decoction, is at least partly mediated through modulation of the profile and/or activity of GM.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PE‐D2 elevated the microorganisms important for maintaining the normal balance of gut microbiota and gut barrier function, particularly Bacteroides, Faecalibacterium, Butyricicoccus, Odoribacter, and Butyricimonas, while decreased the proinflammatory microorganisms including Parvimonas, Methanobrevibacter, and Methanosphaera. They found that PE alleviates endotoxemia in overweight‐obese patients through the modulation of Faecalibacterium, Odoribacter, and Parvimonas (Gonzalez‐Sarrias et al, ).…”
Section: Resultsmentioning
confidence: 99%